CFD Analysis of Supersonic Combustion at Mach 2 with K-E Turbulence Model. Issue 1 (March 2020) - Gupta, K. K.; Singh, A.P.; Roy, Shantanu
Abstract: This In this paper combustion of hydrogen under unsteady and supersonic conditions has been presented. The combustor having an injector for injecting fuel parallel to the base. The main flow is also parallel to the base. Modeling of this supersonic combustion has been done using K-ε model with Finite rate chemistry combustion model. In supersonic combustion time available is very short for proper mixing. Intensity of heat release, duct geometry, injection techniques, and mixture (fuel + oxidizer) quality and flow regime are the predominating parameter which decides the flame stabilization. This numerical result demonstrates that flamelet approach is suitable in supersonic flows. Combustion characteristics for injected fuel and supersonic air flow in combustor are presented in this paper. The result shows that the mixing quality increases flame speed almost linearly. The stagnation temperature reaches up to 2420 k in the combustor.